Growth of columnar gold electrodes by electroreducing hydrous gold oxide layers : Kinetics and mechanistic interpretation - Vela, María Elena (1995)
Rough columnar structured gold electrodeposits were prepared in aqueous 0.5 M M H2SO4 by electroreducing a hydrous gold oxide layer built up on a gold substrate by means of a fast periodic potential routine. The analysis of potentiodynamic and potentiostatic hydrous oxide layer electroreduction data indicated the initial nucleation of gold clusters at the metals|oxide interface. The growth of gold nuclei proceeded under a constant capture area condition for depositing gold ions contained in the hydrous oxide layer. Columnar gold electrodeposition was assisted by the gel-like characteristics of the hydrous gold oxide layer. Gold columnar growth ended as soon as the column tips reached the oxide s| solution interfacc. The proposed kinetic model accounts for the high surface area development and surface fractal properties of this type of metal electrode.